Circadian clock regulates hepatotoxicity of Tripterygium wilfordii through modulation of metabolism. (1st June 2020) - Zhao, Huan; Tong, Yongbin; Lu, Danyi; Wu, Baojian
Abstract: Objectives: We aimed to determine the diurnal rhythm of Tripterygium wilfordii (TW) hepatotoxicity and to investigate a potential role of metabolism and pharmacokinetics in generating chronotoxicity. Methods: Hepatotoxicity was determined based on assessment of liver injury after dosing mice with TW at different circadian time points. Circadian clock control of metabolism, pharmacokinetics and hepatotoxicity was investigated using Clock -deficient ( Clock −/− ) mice. Key findings: Hepatotoxicity of TW displayed a significant circadian rhythm (the highest level of toxicity was observed at ZT2 and the lowest level at ZT14). Pharmacokinetic experiments showed that oral gavage of TW at ZT2 generated higher plasma concentrations (and systemic exposure) of triptolide (a toxic constituent) compared with ZT14 dosing. This was accompanied by reduced formation of triptolide metabolites at ZT2. Loss of Clock gene sensitized mice to TW-induced hepatotoxicity and abolished the time-dependency of toxicity that was well correlated with altered metabolism and pharmacokinetics of triptolide. Loss of Clock gene also decreased Cyp3a11 expression in mouse liver and blunted its diurnal rhythm. Conclusions: Tripterygium wilfordii chronotoxicity was associated with diurnal variations in triptolide pharmacokinetics and circadian expression of hepatic Cyp3a11 regulated by circadian clock. Our findings may have implications for improving TW treatment outcome with a chronotherapeutic approach.